2023
DOI: 10.3389/fpubh.2023.1181591
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of low back pain and its associated factors among traditional cloth weavers in Gulele sub-city, Addis Ababa, Ethiopia

Abstract: The prevalence of work-related musculoskeletal disorders particularly low back pain is significantly high among common informal or small-scale enterprises within developing countries like weaving. However, there is little information on risk factors for low back pain in the informal sector such as the weaving sector in the areas of Addis Ababa as well as in Ethiopia. Therefore this study was aimed to assess the magnitude of low back pain and its associated factors among traditional cloth weavers in the Gulele … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
1
1
Order By: Relevance
“…The present study's findings revealed a higher prevalence than the studies conducted in Central and Southern Ethiopia (48.9%) and the Gulele Sub-city of Addis Ababa (50%) ( 19 , 22 ). This disparity may be due to differences in the sex, age, working hours, and working area of the participants.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…The present study's findings revealed a higher prevalence than the studies conducted in Central and Southern Ethiopia (48.9%) and the Gulele Sub-city of Addis Ababa (50%) ( 19 , 22 ). This disparity may be due to differences in the sex, age, working hours, and working area of the participants.…”
Section: Discussioncontrasting
confidence: 79%
“…Prolonged periods of sitting without any change in posture can weaken abdominal muscles, causing spine curvature and respiratory and digestive disorders ( 18 ). Moreover, age, long hours of work (more than 8 h per day), frequent bending, years of work experience, awkward postures, repetitive movements, lack of back support, 7-day work weeks, job stress, and lack of job satisfaction are all factors associated with LBP ( 19 23 ). Efforts at workplaces to prevent LBP have gained increasing attention over the past years ( 24 ).…”
Section: Introductionmentioning
confidence: 99%